Effect Of 30° Head Level Position Intervention in A Patient with Inefective Cerebral Perfusion: A Case Study - Ningrum, Vica Cahya; Komariah, Mariah; Permana, Rian Hara (Universitas Islam Negeri Alauddin Makassar, 2024)
Meningitis is an infectious disease affecting the membranes surrounding the brain and spinal cord, often presenting with fever, headache, and stiff neck. Effective nursing interventions are crucial for managing the symptoms and improving patient outcomes. This case study examines the impact of positioning a patient with ineffective cerebral perfusion in a 30° semi-Fowler position. The research adopts a case study design using a nursing process approach, which involves monitoring vital signs, respiratory status, neck stiffness, and administering pharmacological treatments in collaboration with healthcare providers. Significant improvements were observed following the intervention. By the fifth day, the patient's consciousness had improved to a Glasgow Coma Scale (GCS) score of 15, indicating a state of compos mentis, with no confusion, headaches, or fever. These findings suggest that the 30° semi-Fowler position can effectively alleviate symptoms and improve cerebral perfusion in patients with meningitis. The analysis indicated a partial resolution of nursing problems, with plans to maintain the patient’s hemodynamic status and continue appropriate drug therapy for optimal recovery. The study highlights the importance of proper patient positioning and collaborative care in managing meningitis and improving patient outcomes Keywords: Meningitis, Nursing Care, Semi Fowler Position, Consciousness Status